1,2,3-Triazoles as leaving groups in SNAr–Arbuzov reactions: synthesis of C6-phosphonated purine derivatives - Kriķis, Kārlis-Ēriks; Novosjolova, Irina; Mishnev, Anatoly; Turks, Māris (Beilstein Journal of Organic Chemistry, 2021)
A new method for C–N bond transformations into C–P bonds was developed using 1,2,3-triazoles as leaving groups in SNAr–Arbuzov reactions. A series of C6-phosphonated 2-triazolylpurine derivatives was synthesized for the first time, with the isolated yields reaching up to 82% in the C–P-bond-forming event. The SNAr–Arbuzov reaction of 2,6-bistriazolylpurines follows the general regioselectivity pattern of the C6-position being more reactive towards substitution, which was unambiguously proved by X-ray analysis of diethyl (9-heptyl-2-(4-phenyl-1H-1,2,3-triazol-1-yl)-9H-purin-6-yl)phosphonate.
Keywords: Arbuzov reaction; 2,6-bistriazolylpurines; nucleophilic aromatic substitution; purinylphosphonates